Percutaneous uniportal full-endoscopic surgery for treating symptomatic lumbar facet joint cysts under local anesthesia combined with monitored anesthesia care: a preliminary report of eight cases with at least 1 year follow-up - Tan, Haining; Yu, Lingjia; Li, Xiang; Yang, Yong; Zhu, Bin (Frontiers in Neurology, 2023)
Background Lumbar facet joint cysts (FJCs) are a relatively rare clinical pathology that can result in radiculopathy or neurogenic claudication. Various treatments such as percutaneous aspiration and surgery have been reported to have good clinical outcomes. However, few clinical studies have aimed to treat symptomatic lumbar FJCs by using uniportal full-endoscopic (UFE) surgery. This study aimed to investigate the preliminary clinical outcomes of UFE surgery for the treatment of lumbar FJCs under local anesthesia combined with monitored anesthesia care (MAC). Methods Eight patients (five males and three females) with symptomatic lumbar FJCs who underwent UFE surgery under local and MAC anesthesia were enrolled in this study between January 2018 and April 2022. The clinical characteristics, radiological features, operative information, visual analog scale (VAS) score, Oswestry disability index (ODI), and overall outcome rating based on the modified MacNab criteria were retrospectively analyzed. Results Of the eight patients, four underwent a transforaminal approach and four underwent an interlaminar approach. Postoperatively, the mean VAS score for leg pain decreased from 6.1 before surgery to 0.6 after surgery, and the ODI decreased from 74.5% to 14.7%. All patients were followed up for more than 1 year, and the good-to-excellent rate based on the modified MacNab criteria remained 100% at the last follow-up. No complications occurred during the follow-up period. Conclusion Lumbar FJCs can cause severe radiating leg pain and/or neurogenic claudication due to the dural sac compression and nerve roots. As an alternative treatment, UFE decompression under local and MAC anesthesia may provide effective clinical outcomes for symptomatic lumbar FJCs.